Analysis Of The Implementation Of Work From Home Mechanism As A Strategy To Improve Work Productivity And Sales Effectiveness At PT. MAP - Fitrianiar Amri; Sampurno A Chaliq; Indah Masri (SEAN Institute, 2024)
The COVID-19 pandemic has forced organizations to change their functional status quo, leading to the new norm of working from home (WFH). WFH has become an increasingly common practice and is an important dimension in the future of work. The implementation of the WFH model has raised issues, particularly in Indonesia, where the WFH culture has not yet become ingrained in organizations. Challenges related to the WFH model include productivity, effectiveness, and sales trends. The impact of implementing the Work From Home (WFH) policy at PT. MAP on work productivity and sales effectiveness has been examined. Despite some coordination and production challenges due to WFH, productivity at PT. MAP remains high. Quality Assurance (QA) analysis from 2020 to 2022 shows an increase in production each year. The implementation of WFH also affected the target and realization of Selling Out, which fluctuated from 2019 to 2022, but exceeded the target in 2022. WFH also influenced direct interactions with users such as doctors, nurses, midwives, and procurement departments in hospitals and pharmacies . Although there was initially a decrease in sales due to adaptation to WFH, sales subsequently increased due to the demand for medicines in the community, especially medicines like those sought for COVID-19 symptoms.External Factor Analysis (EFAS) indicates that the implementation of WFH has a significant potential (60.5%) to enhance work productivity and sales effectiveness, despite some weaknesses (39.5%). Therefore, the implementation of WFH at PT. MAP has a greater strength (73%) than weakness (27%) and still has the potential to become a routine work model, especially at the headquarters.